Ethnic stereotype in mass media of Kazakhstan - Tausogarova A., A.; Ibrayeva Zh., Zh.; Iskakova, G. (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the analysis of the mass media of Kazakhstan and the influence of TV programmes on the beliefs of the viewers. Mass media is considered to be one of the powerful means for constructing stereotypes about ethnic groups. The scientific works of some foreign researchers focused on the study of negative sociocultural stereotypes in mass media were under consideration. The recurrent TV programmes dedicated to the ethnic issues and peculiarities of various nations transmitted on the widely known TV channel in Kazakhstan «Kazakh TV» are studied for the purpose of identification of their effect. The conclusion the authors came to in the result of the analysis is that the TV programmes in Kazakhstani mass media mostly are aimed at forming the sense of tolerance that is a key to peace and broadening the horizon of people enriching their background.